Laser additively manufactured crack-free aluminum-bearing high entropy alloys: alloy design, synthesis, cracking inhibition and microstructure evolution effects on their tensile properties - Jiawang Wu; Yaxiong Guo; Fangping Wang; Xiaojuan Shang; Jing Zhang; Qibin Liu (Virtual and Physical Prototyping, 2023)
Developing high-performance high-entropy alloys (HEAs) fabricated by laser additive manufacturing (LAM) is the pursuit of the metallic community. In the present work, we designed a series of [(Al6-xNbx)-(FeCoNi)12]Cr3 HEA compositions using a high-entropy alloying strategy based on a cluster-plus-glue-atom model. And their thin-wall-sharped bulks were fabricated by LAM and post-aging treatment. The effects of cracking inhibition and microstructure evolution on the tensile properties were researched in detail. The results show that as the Nb substitutes for Al atoms, the cracking behaviour is ameliorated, ascribed to the tiny Laves phase refined the dendrite spacings and back-filled in the inter-dendritic liquid film. Also, introducing Nb atoms improves the strength but deteriorates the ductility. Significantly, the Nb4 HEA possesses the best tensile-property combination (i.e. σs ∼ 419.2 MPa, σb ∼ 787.4 MPa, and δ ∼ 15.5%) with a strain mechanism of dislocation slip mode. After post-aging for 72 h, the microstructure comprises fully recrystallized equiaxed FCC grains and many tiny needle-like D019 precipitates, leading to high strength and sufficient ductility (i.e. σ0.2 ∼ 535.9 MPa, σb ∼820 MPa and δ value of 8.9%). These findings provide a new paradigm for the LAM of crack-free HEAs with excellent mechanical properties.